Optimizing the design of preactivated titanium T-loop springs with Loop software - Martins, Renato Parsekian [UNESP]; Buschang, Peter H.; Martins, Lidia Parsekian [UNESP]; Gandini, Luiz Gonzaga (Mosby-elsevier, 2008)
ATMA (Ormco Corp, Glendora, Calif) T-loop spring (TTLS), preactivated with a gable bend distal to the loop, holds promise for producing controlled tipping of the canines and translation of the posterior segment. However, there is currently no consensus as to where the preactivated gable bend or the loop should be placed, what the height of the loop should be, or how the interbracket distance changes the moments produced. Using the Loop software program (dHal, Athens, Greece), we systematically modified a .017 x .025-in TTLS (10 x 6 mm) that was preactivated with a 45 degrees gable bend distal to the loop, and simulated the effects. As the gable bend was moved posteriorly, the moment increased at the posterior bracket more than it decreased at the anterior bracket. As the loop was brought closer to the anterior bracket, the posterior moment decreased at the same rate that it increased anteriorly. As the loop was increased in size, the moments increased both posteriorly and anteriorly. As the interbracket distance increased, the posterior moment decreased, and the anterior moment remained constant. We concluded that the size of the loop should be slightly increased, to 10 x 7 mm, and it should be placed 2 mm from the anterior bracket, with a preactivation bend of 45 degrees, 4 to 5 mm from the posterior bracket (after 4 mm of activation).